The Impact of Social Pressure on Men's Mental Health - Analysis of Social Expectations from the Perspective of Clinical Psychology - Anna Podolak; Agnieszka Zarotyńska; Justyna Bieniara-Woźnicka (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2025)
The article discusses the impact of social pressure on men's mental health, paying special attention to social expectations from the perspective of clinical psychology. Social pressure, which is a set of norms, values and expectations imposed by family, professional environment or media, can have both positive and negative effects. In men, it often takes the form of expectations regarding strength, independence and emotional resilience. The traditional model of masculinity places men in the role of strong, unweak individuals, which leads to difficulties in expressing emotions and an increased risk of depression, anxiety and self-destructive behavior . Social expectations can cause the so-called "masked depression", which manifests itself in aggression, irritability and addictions, instead of classic depressive symptoms. Moreover, men are less likely than women to seek psychological help, which deepens problems related to emotional isolation and chronic stress. The article emphasizes the importance of changing the approach to masculinity, taking into account greater acceptance of expressing emotions and seeking support. The content of the article indicates the need to adapt preventive and educational activities to the specific needs of men, as well as the need to break the stereotypes of masculinity that make it difficult to use psychological help.